ADOPSI PETANI TERNAK TERHADAP PELAKSANAAN INSEMINASI BUATAN PADA KAMBING KACANG DI KECAMATAN SAWAHAN KABUPATE MADUIN PROPINSI JAWA TIMUR (THE ADOPTION OF LIVESTOCK FARMER AT ARTIFICIAL INSEMINATION EXECUTION OF KACANG GOAT IN SAWAHAN SUB DISTRICT, MADIUN - Kusmiati, Ita; Subekti, Untung; Windari, Wahyu (Jurnal Ilmu-Ilmu Pertanian, 2007)
The goal of this research is to know the adoption level at artificial insemination execution of goat. The survey is executed in Sawahan Sub district, Madiun Regency, East Java, March until April 2007. From 13 villages in Sawahan Sub district that selected by stratified random sampling, obtained 3 villages, Rejosari village with a few livestock ownership criteria, Lebak Ayu (medium livestock ownership), and Sawahan (high livestock ownership). From these village then selected by 30 responders that done by simple random. The adoption level of the livestock farmer marginally at low adoption level. From 30 responders, 6 people at high adoption level, 10 people at medium adoption level, and 14 people at low adoption level. Data processing by using SPSS program that show there is closeness relation among adoption level to knowledge level variable and social characteristic (counseling). So that knowledge of livestock farmer about artificial insemination at goat can increase need existence of counseling that done continually and have continuation, and there is Cooperation with related institution that is Animal Husbandry Office in Madiun Regency in ready of tools.